2003
DOI: 10.1097/00004872-200305000-00023
|View full text |Cite
|
Sign up to set email alerts
|

ST-segment depression in hypertensive patients is linked to elevations in blood pressure, pulse pressure and double product by 24-h Cardiotens monitoring

Abstract: Simultaneous ABPM and ST-segment analysis identifies episodes of silent myocardial ischemia during increases of BP and HR. Hypertensive patients with ischemic heart disease and ST events show higher mean pulse pressure values than are observed in patients without events. A PP of >or= 60 mmHg is linked to an increased risk of silent myocardial ischemias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 32 publications
3
26
0
3
Order By: Relevance
“…A previous study has reported that ST-segment depressions occurred when DP increased from 10,900 (24-h mean) to 14,500 mmHg bpm (during ST-depression) in hypertensive patients (6). In the present study, the number of subjects, whose SAC was equal to or over 14,500 mmHg bpm, appears to have increased with increasing exercise work rate (Fig.…”
Section: Fig 5 Relationships Between Systemic Arterial Compliance (supporting
confidence: 65%
See 1 more Smart Citation
“…A previous study has reported that ST-segment depressions occurred when DP increased from 10,900 (24-h mean) to 14,500 mmHg bpm (during ST-depression) in hypertensive patients (6). In the present study, the number of subjects, whose SAC was equal to or over 14,500 mmHg bpm, appears to have increased with increasing exercise work rate (Fig.…”
Section: Fig 5 Relationships Between Systemic Arterial Compliance (supporting
confidence: 65%
“…Increase in blood pressure and double product (DP: systolic blood pressure [SBP] × heart rate [HR]; an index of myocardial oxygen consumption) as evaluated by 24-h Cardiotens monitoring are demonstrably important determinants of STsegment depression in hypertensive older humans (6). Myocardial oxygen consumption increases during exercise because cardiac output and blood pressure increase.…”
Section: Introductionmentioning
confidence: 99%
“…However, also in that study this association did not remain significant when ambulatory BP data were included in the regression model. A combined elevation of heart rate and pulse pressure has been found to be an important predictor of myocardial ischaemia [42] and cardiovascular mortality [43]. In our sample, the ambulatory heart rate-pulse pressure product was an independent predictor of the future SBP level in the multivariable model.…”
Section: Discussionmentioning
confidence: 53%
“…this is because earlier studies among subjects with ischemic heart disease have found raised RPP to be associated with silent myocardial ischemia, and increased risk for acute myocardial ischemia and cardiovascular mortality. 10,20 One of the limitations of this study is the fact that we could not assess Nt-BNP in all the subjects because of limited funds for the study.…”
Section: Resultsmentioning
confidence: 99%